Computer Performance Engineering 9th European Workshop, EPEW 2012, Munich, Germany, July 30, 2012, and 28th UK Workshop, UKPEW 2012, Edinburgh, UK, July 2, 2012, Revised Selected Papers - Tribastone, Mirco; Gilmore, Stephen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed post-proceedings of the 9th European Performance Engineering Workshop, EPEW 2012, held in Munich, Germany, and the 28th UK Performance Engineering Workshop, UKPEW 2012, held in Edinburgh, UK, in July 2012. The 15 regular papers and one poster presentation paper presented together with 2 invited talks were carefully reviewed and selected from numerous submissions. The papers cover a wide range of topics from classical performance modeling areas such as wireless network protocols and parallel execution of scientific codes to hot topics such as energy-aware computing to unexpected ventures into ranking professional tennis players. In addition to new case studies, the papers also present new techniques for dealing with the modeling challenges brought about by the increasing complexity and scale of systems today.
Trading Power Consumption against Performance by Reserving Blocks of Servers -- Operational Semantics for Product-Form Solution -- Moment Closures for Performance Models with Highly Non-linear Rates -- Scale-Freeness of SPA Models with Weighted Immediate Actions -- Experimental Evaluation of the Performance-Influencing Factors of Virtualized Storage Systems -- Tradeoff between Accuracy and Efficiency in the Time-Parallel Simulation of Monotone Systems -- Compositional Approximate Markov Chain Aggregation for PEPA Models -- A Path Connection Availability Model for MANETs with Random Waypoint Mobility -- Formal Performance Modelling: From Protocols to People -- SRN Models for Analysis of Multihop Wireless Ad Hoc Networks -- Don$1 (Bt Just Go with the Flow: Cautionary Tales of Fluid Flow Approximation -- PCTMC Models of Wireless Sensor Network Protocols -- A Novel Approach to Energy Efficient Content Distribution with BitTorrent -- Performance Modelling of Magnetohydrodynamics Codes -- Optimisation of Patch Distribution Strategies for AMR Applications -- Energy Consumption in the Office -- On the (Page) Ranking of Professional Tennis Players -- Towards a Volunteer Cloud Architecture.s
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer simulation; Engineering economy; Computer Science; System Performance and Evaluation; Software Engineering; Computer Communication Networks; Simulation and Modeling; Energy Economics